Бренд як елемент успішного виконання завдань інформаційного менеджменту - Колесницька, Н. М.; Kolesnycka, N. M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
The author analyzes the concept of information management and the concept of brand and branding. Makes an attempt to define a brand as an effective mechanism for information management tasks.
Brand as a part of successful implementation information management tasks
Н. М. Колесницька, аспірантка кафедри міжнародної інформації НУ «Львівська політехніка» (Україна, м.Львів)
Keywords: information management; brand; branding